Motivations for pre-exposure prophylaxis uptake and decline in an HIV-hyperendemic setting: findings from a qualitative implementation study in Lesotho - Chebet, Joy J.; McMahon-Rössle, Shannon A.; Tarumbiswa, Tapiwa; Hlalele, Hlalele; Maponga, Chivimbiso; Mandara, Esther; Ernst, Kacey; Alaofe, Halimatou; Bärnighausen, Till; Ehiri, John E.; Geldsetzer, Pascal; Nichter, Mark (AIDS research and therapy, 2023)
Background: Pre-Exposure Prophylaxis (PrEP) has demonstrated clinical efficacy in preventing HIV infection, yet its uptake remains low. This study, conducted in five PrEP implementing districts in Lesotho, examined factors motivating persons at risk of HIV infection to adopt or reject PrEP when offered freely. Methods: In-depth interviews were undertaken with stakeholders directly engaged with PrEP policy (n = 5), program implementation (n = 4), and use (current PrEP users = 55, former PrEP users = 36, and PrEP decliners (n = 6)). Focus group discussions (n = 11, 105 total participants) were conducted with health staff directly providing HIV and PrEP services. Results: Demand for PrEP was reported highest among those at greatest risk for HIV acquisition: those in serodiscordant relationships and/or engaged in sex work. Culturally sensitive PrEP counseling was described as an opportunity to transfer knowledge, build trust, and address user concerns. Conversely, top-down counseling resulted in PrEP distrust and confusion about HIV status. Key motivations for PrEP uptake revolved around sustaining core social relationships, desire for safer conception, and caring for ailing relatives. The decline of PrEP initiation was driven by a combination of individual-level factors (risk perception, perceived side effects, disbelief of the drug’s efficacy and PrEP’s daily pill regimen), societal factors (lack of social support and HIV-related stigma), and structural factors related to PrEP access. Conclusions: Our findings suggest strategies for effective national PrEP rollout and implementation include: (1) demand creation campaigns which highlight positive aspects of PrEP, while simultaneously addressing apprehensions for uptake; (2) strengthening health provider counseling capacity; and (3) addressing societal and structural HIV-related stigma.